2020
DOI: 10.1038/s41598-020-69213-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen deposition and phosphorus addition on arbuscular mycorrhizal fungi of Chinese fir (Cunninghamia lanceolata)

Abstract: Nitrogen (N) deposition is a key factor that affects terrestrial biogeochemical cycles with a growing trend, especially in the southeast region of China, where shortage of available phosphorus (P) is particularly acute and P has become a major factor limiting plant growth and productivity. Arbuscular mycorrhizal fungi (AMF) establish a mutualistic symbiosis with plants, and play an important role in enhancing plant stress resistance. However, the response of AMF to the combined effects of N deposition and P ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 40 publications
1
25
0
3
Order By: Relevance
“…Low to medium level increases the AM colonization and sporulation; plant growth and root formation. Higher-level nitrogen fertilizer application reduces AM colonization in plants ( Lin et al., 2020 ). More than optimum potassium concentration, root exudation is decreased and soluble carbohydrates get accumulated in cortex, signaling for AM is hampered.…”
Section: Hindrances To Utilize Amf In Agriculturementioning
confidence: 99%
“…Low to medium level increases the AM colonization and sporulation; plant growth and root formation. Higher-level nitrogen fertilizer application reduces AM colonization in plants ( Lin et al., 2020 ). More than optimum potassium concentration, root exudation is decreased and soluble carbohydrates get accumulated in cortex, signaling for AM is hampered.…”
Section: Hindrances To Utilize Amf In Agriculturementioning
confidence: 99%
“…When sufficient P is available, the plant does not need to share carbon for the maintenance of AM fungi for nutrient acquisition. These conditions lead to minimum colonization and higher plant biomass yield [39]. In our study, phosphorus was omitted from the Hoagland solution to stress the maize plants with low nutrient, as a result plant biomass declined, which in turn increased colonization.…”
Section: Discussionmentioning
confidence: 97%
“…We found the highest number (≈500) of R. irregularis spores when we used half-strength Hoagland solution at regular intervals, and the treatment without P after seven weeks. This may be because low P levels help higher spore production with maximum root colonization percentage [39] as high soil P decreased AM fungal abundance [35]. In each sand particle size grade, spore production and root colonization rate decreased when full-strength Hoagland with 40 µM P was used.…”
Section: Discussionmentioning
confidence: 99%
“…Applying N fertilizer increases mycorrhizal colonization and MGR. AMF colonization is in uenced by the available nutrient contents in soil 29,30 . Our results showed that applying a low level of N fertilizer signi cantly increased AMF colonization and the MGR.…”
Section: Discussionmentioning
confidence: 99%